Stainless steel with excellent surface conductivity for fuel cell separator and method for manufacturing the same

By forming an oxide layer with conductor characteristics on the surface of stainless steel, the problem of insufficient surface conductivity in fuel cell separators is solved, and efficient conductivity improvement and cost reduction are achieved.

CN114930583BActive Publication Date: 2025-01-17POHANG IRON & STEEL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202080093019.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-19
Filing Date
2020-10-19
Publication Date
2025-01-17
Estimated Expiration
2040-10-19

AI Technical Summary

Technical Problem

The surface conductivity of existing stainless steel is insufficient in fuel cell separators, and conventional methods cannot effectively reduce the through-plane resistance of the passivation layer, resulting in low productivity and increased costs.

Method used

X-ray angle resolution photoelectron energy spectrum to measure the surface oxide atomic ratio and band gap energy of stainless steel, combined with the surface treatment of non-oxidizing and oxidizing acid solutions, form a surface oxide layer with conductor characteristics to ensure that the surface oxide atomic ratio reaches 0.08 or greater, the band gap can be 2eV or less, achieving ohmic contact.

Benefits of technology

It significantly improves the surface conductivity of stainless steel, is suitable for fuel cell separators, reduces the through-plane resistance of the passivation layer, and improves production efficiency and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114930583B_ABST
    Figure CN114930583B_ABST
Patent Text Reader

Abstract

Disclosed in this specification is a stainless steel with excellent surface conductivity for a fuel cell separator. According to one embodiment, the stainless steel with excellent surface conductivity for a fuel cell separator disclosed herein can have a value of 0.08 or greater for the following surface oxide element ratio (1) measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron emission angle of 12° to 85° on the surface of a stainless steel containing 15 wt% or more Cr. #imgabs0#(I)Cr hydroxide refers to CrOOH, Cr(OH)2 or Cr(OH)3. All oxides and hydroxides include Cr oxide, the Cr hydroxide, Fe oxide, Fe hydroxide and metal oxide (MO); metal oxide (MO) covers mixed oxides, M refers to alloy elements other than Cr and Fe in the matrix material, or a combination thereof; and O represents oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to stainless steel having excellent surface conductivity and a method for manufacturing the same, and more particularly to stainless steel having excellent surface conductivity for a fuel cell separator and a method for manufacturing the same. Background Art

[0002] Stainless steel is considered as a material for electronic components and fuel cell separators due to its excellent corrosion resistance and ease of processing. However, conventional stainless steel has a problem of insufficient electrical conductivity because a passivation layer formed on the surface acts as a through-plane resistance factor.

[0003] To date, the mechanism of the influence of the passivation layer on the surface conductivity of stainless steel has not been clearly determined. Ni plating can be performed on materials for electronic components to improve the surface conductivity of such a passivation layer, or a process of coating a conductive material such as gold, carbon, and nitride on the surface of stainless steel has been proposed to reduce the high contact resistance of stainless steel used for fuel cell separators. However, there is a problem of increased manufacturing cost and time due to Ni plating or additional processes for coating with other coating materials, thereby deteriorating productivity, and the problem that the fundamental through-plane resistance of the passivation layer may not be reduced.

[0004] Furthermore, as another method for improving the surface conductivity of stainless steel, a method of refining the surface of stainless steel has been attempted.

[0005] Patent Document 1 discloses stainless steel for separators having low interface contact resistance and high corrosion potential by controlling a surface refining process.

[0006] Patent Document 2 discloses a method for producing stainless steel having excellent corrosion resistance and low contact resistance by immersing stainless steel containing 17 wt % to 23 wt % of Cr in a [HF] ≥ [HNO 3 ] solution.

[0007] Patent Document 3 discloses stainless steel containing 15 to 45 wt % of Cr and 0.1 to 5 wt % of Mo, wherein the atomic ratio of Cr to Fe contained in a passive layer of the stainless steel is 1 or more.

[0008] However, the methods disclosed in Patent Documents 1 to 3 have limitations because the fundamental through-plane resistance of the passive layer of stainless steel cannot be reduced only by controlling the Cr / Fe atomic ratio of the passive layer in a region of several nm.

[0009] (Patent Document 0001) Korean Patent Application Publication No. 10-2014-0081161 (July 1, 2014)

[0010] (Patent Document 0002) Korean Patent Application Publication No. 10-2013-0099148 (September 5, 2013)

[0011] (Patent Document 0003) Japanese Patent Application Laid-Open No. 2004-149920 (May 27, 2004) Summary of the invention

[0012] Technical issues

[0013] To solve the above problems, a stainless steel for a fuel cell separator having excellent surface conductivity and a method for manufacturing the stainless steel for a fuel cell separator which is suitable for an electrical contact material and a fuel cell separator material is provided.

[0014] Technical Solution

[0015] In order to achieve the above-mentioned purpose, according to one aspect of the present disclosure, a stainless steel with excellent surface conductivity for a fuel cell separator is provided, wherein the value of the following surface oxide atomic ratio (1) measured on the surface of the stainless steel containing 15 wt % or more Cr by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source under the condition that the emission angle of the photoelectrons is 12° to 85° can be 0.08 or greater.

[0016] (1)

[0017] Cr hydroxide means CrOOH, Cr(OH) 2 or Cr(OH) 3. All oxides and hydroxides include Cr oxide, Cr hydroxide, Fe oxide, Fe hydroxide and metal oxide (MO), and metal oxide (MO) encompasses mixed oxides, wherein M represents alloying elements or combinations thereof other than Cr and Fe in the matrix, and O represents oxygen.

[0018] In the stainless steel having excellent surface conductivity for a fuel cell separator of the present disclosure, the value of the surface oxide atomic ratio (1) may be 0.2 or more.

[0019] In the stainless steel having excellent surface conductivity for a fuel cell separator of the present disclosure, the band gap energy of a surface oxide layer of the stainless steel may be 2 eV or less.

[0020] In the stainless steel having excellent surface conductivity for a fuel cell separator of the present disclosure, a surface oxide layer of the stainless steel may form an ohmic contact with a substrate.

[0021] To achieve the above-mentioned object, according to another aspect of the present disclosure, there is provided a method for manufacturing stainless steel having excellent electrical conductivity for a fuel cell separator, the method comprising: a primary surface treatment, the primary surface treatment being performed by immersing a cold-rolled stainless steel plate in a non-oxidizing acid solution or performing an electrolytic treatment after the immersion; and a secondary surface treatment, the secondary surface treatment being performed by immersing the cold-rolled stainless steel plate in an oxidizing acid solution, wherein the value of the following surface oxide atomic ratio (1) measured on the surface of stainless steel containing 15 wt % or more of Cr by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source under the condition that the emission angle of the photoelectrons is 12° to 85° can be 0.08 or greater.

[0022] (1)

[0023] Cr hydroxide means CrOOH, Cr(OH) 2 or Cr(OH) 3. All oxides and hydroxides include Cr oxide, Cr hydroxide, Fe oxide, Fe hydroxide and metal oxide (MO), and metal oxide (MO) encompasses mixed oxides, wherein M represents an alloying element or a combination thereof other than Cr and Fe in the matrix, and O represents oxygen.

[0024] In the method for manufacturing stainless steel having excellent surface conductivity for a fuel cell separator, a primary surface treatment is performed by immersing a cold-rolled stainless steel sheet in a non-oxidizing acid solution for 5 seconds or longer, or by heating the cold-rolled stainless steel sheet at 0.1 A / cm 2 The electrolytic treatment is carried out at a current density of or greater for 5 seconds or longer, and the non-oxidizing acid solution may be a 5 wt % or greater hydrochloric acid solution or a sulfuric acid solution at 50° C. or higher.

[0025] In the method for manufacturing stainless steel with excellent surface conductivity for fuel cell separators, the secondary surface treatment includes immersing the cold-rolled stainless steel sheet in an oxidizing acid solution for 5 seconds or longer, and the oxidizing acid solution may be a 5 wt % or greater nitric acid solution at 50° C. or higher.

[0026] Beneficial Effects

[0027] The present disclosure can provide stainless steel for fuel cell separators having excellent surface conductivity and a manufacturing method thereof, which is suitable for electrical contact materials and fuel cell separator materials, by making a surface oxide layer formed on the surface of the stainless steel and having semiconductor characteristics into a conductor.

[0028] The present disclosure can also provide stainless steel for fuel cell separators having excellent surface conductivity and a band gap energy of a surface oxide layer of 2 eV or less by controlling the value of the following surface oxide atomic ratio (1) measured on the surface of the stainless steel by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source under conditions where the emission angle of the photoelectrons is 12° to 85° to 0.08 or greater.

[0029] (1)

[0030] Cr hydroxide means CrOOH, Cr(OH) 2 or Cr(OH) 3. All oxides and hydroxides include Cr oxide, Cr hydroxide, Fe oxide, Fe hydroxide and metal oxide (MO), and metal oxide (MO) encompasses mixed oxides, wherein M represents alloying elements or combinations thereof other than Cr and Fe in the matrix, and O represents oxygen.

[0031] According to the present disclosure, a surface oxide layer of stainless steel can form an ohmic contact with a substrate, thereby providing stainless steel having excellent surface conductivity for a fuel cell separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1a and Figure 1b Referring to the results in Table 2, this is a graph showing the relationship between the band gap energy and the surface oxide atomic ratio (1). DETAILED DESCRIPTION

[0033] A stainless steel having excellent surface conductivity for a fuel cell separator is provided, wherein the value of the following surface oxide atomic ratio (1) measured on the surface of the stainless steel containing 15 wt % or more Cr by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source under the condition that the emission angle of the photoelectrons is 12° to 85° can be 0.08 or greater.

[0034] (1)

[0035] Cr hydroxide means CrOOH, Cr(OH) 2 or Cr(OH) 3. All oxides and hydroxides include Cr oxide, Cr hydroxide, Fe oxide, Fe hydroxide and metal oxide (MO), and metal oxide (MO) encompasses mixed oxides, wherein M represents alloying elements or combinations thereof other than Cr and Fe in the matrix, and O represents oxygen.

[0036] Embodiments of the invention

[0037] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. However, the embodiments of the present disclosure may be implemented in many different forms and should not be understood to be limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure will be detailed and complete, and will fully convey the concept of the present invention to those skilled in the art.

[0038] In addition, the terms used herein are only used to describe specific embodiments. Unless otherwise specified, expressions used in the singular include plural expressions. Throughout the specification, terms such as "including" or "having" are intended to indicate the presence of the features, operations, functions, components or combinations thereof disclosed in the specification, and are not intended to exclude the possibility that one or more other features, operations, functions, components or combinations thereof may exist or may be added.

[0039] Meanwhile, unless otherwise defined, all terms used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present disclosure belongs. Therefore, unless explicitly defined as such herein, these terms should not be interpreted in an idealized or excessive sense. As used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form.

[0040] The terms "about", "substantially" and the like used throughout the specification mean that when natural manufacturing and material allowable errors are proposed, such allowable errors correspond to the value or are similar to the value, and such values ​​are intended for clear understanding of the present invention or for preventing unintentional infringers from illegally using the disclosure of the present invention.

[0041] In addition, as used herein, the term "cold-rolled stainless steel plate" refers to a cold-rolled stainless steel plate manufactured by a common manufacturing method for stainless steel including hot rolling-heating-cold rolling-annealing, and can be interpreted as a cold-rolled stainless steel plate manufactured by a common method for manufacturing cold-rolled stainless steel plates within the scope clearly recognized by those skilled in the art.

[0042] In addition, as used herein, the term "surface oxide" refers to an oxide formed on the surface of stainless steel as a result of spontaneous oxidation of metal elements contained in the matrix by external oxygen when the stainless steel is exposed to a temperature of about 200° C. or less. The surface oxide may include Cr2O3 as a main element and may include SiO2, SiO, Si2O3, MnO, MnO2, Mn2O3, VO, V2O3, V2O5, NbO, NbO2, Nb2O5, TiO2, FeO, Fe2O3, and Fe3O4. Although examples of surface oxides are given above, it should be noted that these examples are given for illustrative purposes only, and the present disclosure should not be construed as being limited to these examples.

[0043] Furthermore, as used herein, the term "surface oxide layer" refers to a layer including a surface oxide according to the present disclosure and may also be construed as a passivation layer of stainless steel.

[0044] In addition, as used herein, "Fe oxide" refers to any Fe oxide in the form of an oxide of Fe within the scope that can be clearly recognized by a person skilled in the art, such as FeO, Fe2O3, and Fe3O4. "Fe hydroxide" refers to any Fe hydroxide in the form of a hydroxide of Fe within the scope that can be clearly recognized by a person skilled in the art, such as FeOOH, Fe(OH)2-, and Fe(OH)3.

[0045] In addition, as used herein, “Cr oxide” refers to any Cr oxide in the form of an oxide of Cr within the range that can be clearly recognized by a person of ordinary skill in the art, such as Cr 3 O 4 , Cr 2 O 3 , CrO 2 , and CrO 3 .

[0046] It is known that the passivation layer of conventional stainless steel has high resistance due to the semiconductor characteristics of oxide. The present inventors have developed a stainless steel having excellent surface conductivity for fuel cell separators suitable for electrical contacts and fuel cell separator materials by making the surface oxide layer having semiconductor characteristics into a conductor by controlling the band gap energy of the surface oxide layer to 2 eV or less.

[0047] According to one embodiment of the present disclosure, the value of the following surface oxide atomic ratio (1) measured on the surface of stainless steel by angle-resolved photoemission spectroscopy (ARPES) using an Al-Kα X-ray source under the condition that the emission angle of the photoelectrons is 12° to 85° may be 0.08 or more.

[0048] (1)

[0049] Cr hydroxide means CrOOH, Cr(OH) 2 or Cr(OH) 3. All oxides and hydroxides include Cr oxide, Cr hydroxide, Fe oxide, Fe hydroxide and metal oxide (MO), and metal oxide (MO) encompasses mixed oxides, wherein M represents alloying elements or combinations thereof other than Cr and Fe in the matrix, and O represents oxygen.

[0050] The metal oxide (MO) may be, for example, SiO2, SiO, Si2O3, MnO, MnO2, Mn2O3, VO, V2O3, V2O5, NbO, NbO2, Nb2O5, or TiO2. Although examples of metal oxides (MO) are listed above, these examples are only intended to illustrate the present disclosure in more detail and are not intended to limit the scope of the present disclosure.

[0051] Hereinafter, the reason for the numerical limitation on the exit angle of photoelectrons in X-ray angle-resolved photoelectron spectroscopy will be described, and then the reason for the numerical limitation on the surface oxide atomic ratio (1) will be described.

[0052] In X-ray angle-resolved photoelectron spectroscopy, as the emission angle of photoelectrons decreases, the analysis depth from the outermost surface of the stainless steel in the depth direction decreases, and as the emission angle increases, the analysis depth increases. In view of this, regardless of the thickness of the stainless steel, in order to analyze the composition of all oxides formed on the surface of the stainless steel, according to one embodiment, the surface of the stainless steel can be measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source under conditions where the emission angle of the photoelectrons is 12° to 85°.

[0053] The reason why the value of the surface oxide atomic ratio (1) measured under the above conditions is limited to 0.08 or more is that the passivation layer is a critical point for conversion from semiconductor characteristics to conductor characteristics. When the value of the surface oxide atomic ratio (1) is less than 0.08, stainless steel is unsuitable due to the semiconductor characteristics of the passivation layer. In order to obtain stainless steel having excellent surface conductivity, it is preferred to control the value of the surface oxide atomic ratio (1) to 0.08 to 0.6.

[0054] In the present disclosure, by controlling the value of the surface oxide atomic ratio (1) to 0.08 or more, the band gap energy of the surface oxide layer can be adjusted to 2 eV or less. When the band gap energy is 0 eV, the surface oxide layer has conductor properties. When the band gap energy is greater than 0 eV and not greater than 2 eV, the surface oxide layer has intermediate properties between semiconductor properties and conductor properties, and thus stainless steel can be suitable for fuel cell separators.

[0055] Furthermore, according to the present disclosure, it is preferred to control the value of the surface oxide atomic ratio (1) to 0.2 or more to adjust the band gap energy of the surface oxide layer to 0 eV. The band gap energy of the surface oxide layer being 0 eV means that although the passivation layer is composed of oxides, the substrate forms a new ohmic contact with the surface oxide layer of the stainless steel, which was previously unknown. In other words, this means that a new conductive coating is formed in which the surface oxide layer forms an ohmic contact with the substrate of the stainless steel.

[0056] In the stainless steel with excellent surface conductivity for fuel cell separator according to the present disclosure, the band gap energy of the surface oxide layer can be 2eV or less, and the steel type is not particularly limited. According to one embodiment, austenitic stainless steel, ferritic stainless steel and ferrite-austenite duplex stainless steel can be used as the stainless steel of the present disclosure.

[0057] In addition, the composition of the alloying elements of the stainless steel with excellent surface conductivity for fuel cell separators according to the present disclosure is not particularly limited. However, the preferred composition is as follows. On the other hand, it should be noted that the composition of the following alloying elements is only intended to help understand the present disclosure in more detail and is not intended to limit the scope of the present disclosure.

[0058] According to one embodiment, the stainless steel according to the present disclosure may include, in terms of weight percentage (wt%), greater than 0% and not more than 0.3% C, greater than 0% and not more than 0.3% N, greater than 0% and not more than 0.7% Si, greater than 0% and not more than 10% Mn, greater than 0% and not more than 0.04% P, greater than 0% and not more than 0.02% S, 15% to 34% Cr, 25% or less Ni, and Fe and other inevitable impurities in the remainder.

[0059] Hereinafter, the reason for numerical limitation on the content of the alloy components in the embodiment of the present disclosure will be described. Hereinafter, unless otherwise specified, the unit is weight %.

[0060] C: greater than 0% and not greater than 0.3%, N: greater than 0% and not greater than 0.3%

[0061] C and N combine with Cr contained in the steel to form Cr carbonitrides, and thus a region in which Cr is locally depleted may be formed, thereby increasing the risk of corrosion resistance degradation. Therefore, it is preferred to control the contents of both elements as low as possible. Therefore, in the present disclosure, the contents of C and N are controlled so that the C content is greater than 0% and not greater than 0.3%, and the N content is greater than 0% and not greater than 0.3%.

[0062] Si: more than 0% and not more than 0.7%

[0063] Si is an element effective for deoxidation. However, excessive Si may deteriorate toughness and formability, and oxide SiO2 generated during the annealing process deteriorates conductivity and hydrophilicity. In view of this, the Si content is controlled to be greater than 0% and not greater than 0.7% in the present disclosure.

[0064] Mn: greater than 0% and not greater than 10%

[0065] Mn is an element effective for deoxidation. However, MnS, which is a Mn inclusion, reduces corrosion resistance, and therefore the Mn content is controlled to be greater than 0% and not greater than 10% in the present disclosure.

[0066] P: greater than 0% and not greater than 0.04%

[0067] Since P deteriorates not only corrosion resistance but also toughness, the P content is controlled to be greater than 0% and not greater than 0.04% in the present disclosure.

[0068] S: greater than 0% and not greater than 0.02%

[0069] S combines with Mn contained in steel to form stable MnS, and the formed MnS acts as a starting point for corrosion to deteriorate corrosion resistance, and therefore it is preferred to control the S content as low as possible. In view of this, the S content can be controlled to be greater than 0% and not greater than 0.02% in the present disclosure.

[0070] Cr: 15% to 34%

[0071] Cr is an element that improves corrosion resistance. Cr is actively added to obtain corrosion resistance in a fuel cell in a strongly acidic operating environment. However, excessive Cr may deteriorate toughness, and therefore in consideration of this, the Cr content is controlled to 15% to 34% in the present disclosure.

[0072] Ni: 25% or less

[0073] Ni is an element that stabilizes the austenite phase and improves corrosion resistance. In addition, Ni is generally contained in austenitic stainless steel and ferrite-austenite duplex stainless steel in an amount greater than a certain amount. However, excessive Ni may deteriorate workability, and therefore in consideration of this, the Ni content is controlled to 25% or less in the present disclosure.

[0074] The lower limit of Ni is not particularly limited, and Ni may be appropriately contained depending on the type of steel. For example, the lower limit of the Ni content in austenitic stainless steel or ferrite-austenite duplex stainless steel may be 2.0% or more. For example, the lower limit of the Ni content in ferritic stainless steel may be less than 2.0%, preferably 1.0% or less, and more preferably 0.01% or less.

[0075] In addition, if necessary, in addition to the above-mentioned alloying elements, the stainless steel according to one embodiment may contain at least one selected from the following as an optional alloying element in terms of weight percentage (wt%): greater than 0.01% and not more than 1.5% Cu, greater than 0.01% and not more than 0.6% V, 0.01% to 5.0% Mo, 0.01% to 0.5% Ti, and 0.01% to 0.4% Nb. However, it should be noted that the composition of the optional alloying elements is only intended to help understand the present disclosure in more detail and is not intended to limit the scope of the present disclosure.

[0076] Cu: more than 0.01% and not more than 1.5%

[0077] Cu is an element that improves corrosion resistance. However, when an excessive amount of Cu is added, Cu is eluted to deteriorate the performance of the fuel cell. Therefore, in consideration of this, the Cu content is controlled to be greater than 0% and not greater than 1.5% in the present disclosure.

[0078] V: greater than 0.01% and not greater than 0.6%

[0079] V is an element that improves the life of a fuel cell by suppressing the elution of Fe in the operating environment of the fuel cell. However, excessive V deteriorates toughness, and therefore in consideration of this, the V content is controlled to be greater than 0.01% and not greater than 0.6% in the present disclosure.

[0080] Mo: 0.01% to 5.0%

[0081] Mo is an element that improves corrosion resistance. However, excessive Mo deteriorates workability, and therefore the Mo content is controlled to 0.01% to 5.0%.

[0082] Ti: 0.01% to 0.5%, Nb: 0.01% to 0.4%

[0083] Ti and Nb combine with C and N contained in the steel to form stable carbonitrides and suppress the formation of a region in which Cr is locally depleted, thereby improving corrosion resistance. However, excessive Ti and Nb deteriorate toughness, and therefore in view of this, the present disclosure controls the Ti content within a range of 0.01% to 0.5%, and controls the Nb content within a range of 0.01% to 0.4%.

[0084] The remaining component of the composition of the present disclosure is iron (Fe). However, the composition may contain undesirable impurities that are inevitably incorporated from the raw materials or the surrounding environment, and therefore the addition of further alloying components cannot be excluded. Impurities are not specifically mentioned in the present disclosure, as they are known to any technician in the manufacturing field.

[0085] The method of manufacturing the stainless steel having excellent surface conductivity for a fuel cell separator according to the present disclosure is not particularly limited as long as the value of the surface oxide atomic ratio (1) is controlled to be 0.08 or more.

[0086] According to one embodiment of the present disclosure, stainless steel with excellent surface conductivity for fuel cell separators can be manufactured by surface treating a cold-rolled steel sheet prepared according to a common stainless steel manufacturing method. The surface treatment according to one embodiment can be performed in two steps, and the primary surface treatment can include immersing the cold-rolled stainless steel sheet in a non-oxidizing acid solution or performing an electrolytic treatment after immersion. The secondary surface treatment can include immersing the cold-rolled stainless steel sheet in an oxidizing acid solution.

[0087] The primary surface treatment according to one embodiment of the present disclosure may include immersing the cold-rolled stainless steel sheet in a non-oxidizing acid solution for 5 seconds or longer, or heating the cold-rolled stainless steel sheet at 0.1 A / cm 2 The electrolytic treatment is performed at a current density of 50° C. or more for 5 seconds or more. In this case, the non-oxidizing acid solution may be a 5 wt % or more hydrochloric acid solution (HCl) or a sulfuric acid solution (H 2 SO 4 ) at 50° C. or more.

[0088] The secondary surface treatment according to one embodiment of the present disclosure may include immersing the cold-rolled stainless steel sheet in an oxidizing acid solution for 5 seconds or longer. In this case, the oxidizing acid solution may be a nitric acid (HNO3) solution of 5 wt% or more at 50°C or higher.

[0089] Hereinafter, the present disclosure will be described in more detail by way of examples. However, it should be noted that the following examples are only intended to illustrate the present disclosure in more detail and are not intended to limit the scope of the present disclosure. This is because the scope of the present disclosure is determined by the matters described in the claims and matters that can be reasonably inferred therefrom.

[0090] Example

[0091] The steel grades having the composition of the alloy elements shown in Table 1 were prepared into slabs by steelmaking and continuous casting. Then, the manufactured slabs were hot rolled at 1200° C. to a thickness of 4.5 mm to obtain hot rolled steel sheets. The hot rolled steel sheets were repeatedly heated and cold rolled at 1050° C. and annealed at 1000° C. to prepare 0.15 mm thick cold rolled steel sheets.

[0092] In the following Table 1, Steels 1 to 9 are invention steels. Steels 1 to 3 are ferritic stainless steels, Steels 4 to 6 are austenitic stainless steels, and Steels 7 to 9 are ferrite-austenite duplex stainless steels. Steels 10 and 11 are comparative steels in which the Cr content is less than 15 wt%.

[0093] Table 1

[0094]

[0095] The cold-rolled steel sheet manufactured according to Table 1 is surface treated under the surface treatment conditions shown in Table 2 below. The surface treatment is performed by primary surface treatment and secondary surface treatment under conditions A to H shown in Table 2. The primary surface treatment is performed by immersing the cold-rolled steel sheet in a sulfuric acid solution as a non-oxidizing acid solution, or performing an electrolytic treatment after the immersion. The secondary surface treatment is performed by immersing the stainless steel in a nitric acid solution as an oxidizing acid solution. For better understanding, as an example of the surface treatment shown in Table 2, the cold-rolled stainless steel sheet of Invention Example 1 of Table 2 is immersed in an 8 wt % sulfuric acid solution at 50°C for 5 seconds for primary surface treatment (A), and then immersed in a 10 wt % nitric acid solution at 50°C for 9 seconds for secondary surface treatment (D).

[0096] The value of the surface oxide atomic ratio (1) of Table 2 is a value obtained using the following expression (1), i.e., a value obtained by measuring the surface of each of the stainless steels according to the inventive examples and the comparative examples using an Al-Kα X-ray source through X-ray angle-resolved photoelectron spectroscopy under the conditions in which the emission angle of the photoelectrons is as shown in Table 2.

[0097] (1)

[0098] The value of the surface oxide atomic ratio (1) was measured using the following method. First, analysis was performed using a PHI Quantera II device under the conditions of the exit angles in Table 2, and peaks were separated from the analysis results based on the binding energies of metal oxides (MO), Cr oxides, Cr hydroxides, Fe oxides, and Fe hydroxides using CasaXPS software, and the atomic concentrations were calculated using CasaXPS software.

[0099] The 'sum of atomic concentrations (atomic %) of Cr in Cr hydroxide' used to obtain the value of the surface oxide atomic ratio (1) is obtained by separating peaks from the Cr hydroxide according to the binding energy and fitting the Cr 2p spectrum to obtain the sum of atomic concentrations (atomic %) of Cr. In this regard, Cr hydroxide means CrOOH, Cr(OH)2 or Cr(OH)3.

[0100] The 'sum of the atomic concentrations (atomic %) of metal elements in all oxides and hydroxides' used to obtain the value of the surface oxide atomic ratio (1) is obtained by adding the 'sum of the atomic concentrations (atomic %) of Cr in Cr oxides', the 'sum of the atomic concentrations (atomic %) of metal elements in metal oxides (MO)', and the 'sum of the atomic concentrations (atomic %) of Fe in Fe oxides and Fe hydroxides' to the sum of the atomic concentrations (atomic %) of Cr in the above-mentioned Cr hydroxides.

[0101] The 'sum of atomic concentrations (atomic %) of Cr in Cr oxides' is obtained by separating peaks from Cr oxides according to the binding energy of Cr and fitting the peaks to the Cr 2p spectrum. The "sum of atomic concentrations (atomic %) of metal elements in metal oxides (MO)" used is obtained by separating peaks according to the binding energy of metal oxides (MO) and fitting the peaks to the spectra of various metals (M) to obtain the sum of atomic concentrations (atomic %) of metal elements. In this regard, metal oxides (MO) encompass mixed oxides, M represents alloying elements or combinations thereof other than Cr and Fe in the matrix; and O represents oxygen. The "sum of atomic concentrations (atomic %) of Fe in Fe oxides and Fe hydroxides" is obtained by separating peaks according to the binding energy of Fe oxides and Fe hydroxides and fitting the peaks to the Fe 2p spectrum to obtain the sum of atomic concentrations (atomic %) of Fe.

[0102] The band gap energy of Table 2 refers to the band gap energy of the surface oxide layer. The band gap energy of the surface oxide layer is measured by using a current sensing atomic force microscope (model Keysight 9500). The stainless steel of the invention example and the comparative example was cut into samples with a size of 1 cm×1 cm, and the band gap energy was measured in a current tip mode while the bias voltage applied by a 20nN load was changed from -10V to 10V in a nitrogen atmosphere with a relative humidity of 18%, so that the surface oxide layer in an inactive state was measured. By measuring a 50μm×50μm area in the sample 5 times, the width of the area where the current detected was "0" when the applied bias voltage was changed from -10V to 10V was used as the band gap energy. In this case, a silicon tip (Si tip) coated with platinum with a thickness of 30nm was used as the tip.

[0103] Table 2

[0104]

[0105]

[0106]

[0107] Hereinafter, stainless steels according to the inventive examples and the comparative examples are compared and evaluated with reference to Table 2. Referring to the results of Table 2, under the surface treatment conditions according to the present disclosure, i.e., under the conditions where the emission angle of the photoelectrons is 12° to 85°, inventive examples 1 to 18 satisfy the value of the surface oxide atomic ratio (1) of 0.08 or more, and thus the band gap energy of the surface oxide layer is not more than 2.0 eV. In addition, with reference to inventive examples 1, 2, 6, 11, 12, 14, 15 and 16, in order to form an ohmic contact between the surface oxide layer and the substrate by adjusting the band gap energy of the surface oxide layer to 0 eV, the value of the surface oxide atomic ratio (1) may be 0.2 or more.

[0108] In Comparative Examples 1 and 2, one surface treatment was performed for a period of time that was too short, 3 seconds, and the value of the surface oxide atomic ratio (1) under the conditions where the emission angle of photoelectrons was 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0109] In Comparative Example 3, the primary surface treatment was performed for a period of time that was too short, 3 seconds, and the secondary surface treatment was not performed. In addition, the value of the surface oxide atomic ratio (1) under the conditions where the exit angle of the photoelectron was 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0110] In Comparative Example 4, no surface treatment was performed, and the value of the surface oxide atomic ratio (1) under the conditions where the emission angles of photoelectrons were 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0111] In Comparative Example 5, the primary surface treatment and the secondary surface treatment were performed for a period of time that was too short, 3 seconds, and the value of the surface oxide atomic ratio (1) under the conditions where the emission angles of photoelectrons were 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0112] In Comparative Examples 6 and 7, the primary surface treatment was performed for a period of time that was too short, 3 seconds, and the secondary surface treatment was not performed. In addition, the value of the surface oxide atomic ratio (1) under the conditions where the exit angle of the photoelectrons was 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0113] In Comparative Example 8, the primary surface treatment and the secondary surface treatment were performed for a period of time that was too short, 3 seconds, and the value of the surface oxide atomic ratio (1) under the conditions where the emission angles of photoelectrons were 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0114] In Comparative Example 9, the primary surface treatment was not performed, and the secondary surface treatment was performed for a period of time that was too short, 3 seconds. In addition, the value of the surface oxide atomic ratio (1) under the conditions where the emission angle of the photoelectrons was 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0115] In Comparative Examples 10 and 11, the primary surface treatment and the secondary surface treatment were performed for a period of time that was too short, 3 seconds. In addition, the Cr content was less than 15 wt %, and the value of the surface oxide atomic ratio (1) under the conditions where the exit angle of the photoelectron was 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0116] In Comparative Example 12, the primary surface treatment was not performed, and the secondary surface treatment was performed for a period of time that was too short, 3 seconds. In addition, the Cr content was less than 15 wt %, and the value of the surface oxide atomic ratio (1) under the conditions where the exit angle of the photoelectron was 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0117] In Comparative Example 13, although the primary surface treatment and the secondary surface treatment were performed for 5 seconds or longer, the Cr content was less than 15 wt %, and the value of the surface oxide atomic ratio (1) under the conditions where the emission angles of photoelectrons were 12°, 44°, and 85° was less than 0.08. Therefore, the band gap energy of the surface oxide layer exceeded 2.0 eV.

[0118] Figure 1a and Figure 1b This is a graph showing the relationship between the band gap energy and the value of the surface oxide atomic ratio (1) based on the results shown in Table 2. Figure 1a and Figure 1b In the example, the emission angles of the photoelectrons are 12° and 85° respectively. Figure 1a and Figure 1b The horizontal axis represents the value of the surface oxide atomic ratio (1), and the vertical axis represents the band gap energy (eV).

[0119] Reference Figure 1a and Figure 1b , it can be determined that when the value of the surface oxide atomic ratio (1) is not less than 0.08 (which is a reference point), the band gap energy is 2 eV or less. When the value of the surface oxide atomic ratio (1) is less than 0.08, the band gap energy increases rapidly, thereby exceeding 2 eV. Referring to this, it can be seen that by controlling the value of the surface oxide atomic ratio (1) to 0.08 or more, the band gap energy can be adjusted to 2 eV or less. In addition, referring to Figure 1a and Figure 1b, it can be confirmed that the value of the surface oxide atomic ratio (1) can be preferably adjusted to 0.08 or more to obtain a band gap energy of 0 eV.

[0120] In addition, Figure 1a and Figure 1b The region marked by the dotted line in represents a region where the value of the surface oxide atomic ratio (1) is not less than 0.08 and the band gap energy is not greater than 2 eV. Figure 1a and Figure 1b , all invention examples are included in Figure 1a and Figure 1b , and thus it can be seen that by controlling the value of the surface oxide atomic ratio (1) to 0.08 or more, a stainless steel having excellent surface conductivity and a band gap energy of 2 eV or less for a fuel cell separator can be provided.

[0121] Based on the results of the above embodiments, by making a surface oxide layer formed on the surface of stainless steel and having semiconductor properties into a conductor, the present disclosure can provide stainless steel with excellent surface conductivity for fuel cell separators and a method for manufacturing the same, wherein the stainless steel is suitable for electrical contact materials and fuel cell separator materials.

[0122] In addition, by controlling the value of the surface oxide atomic ratio (1) measured on the surface of stainless steel by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source under the condition that the emission angle of the photoelectrons is 12° to 85° to 0.08 or greater, a stainless steel having excellent surface conductivity and a band gap energy of a surface oxide layer of 2 eV or less for a fuel cell separator can be provided.

[0123] While the present disclosure has been described in detail with reference to exemplary embodiments, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the present disclosure.

[0124] Industrial Applicability

[0125] The stainless steel having excellent surface conductivity according to the present disclosure may be applied to a fuel cell separator and the like.

Claims

1. A stainless steel having excellent surface conductivity for a fuel cell separator, in, The value of the following surface oxide atomic ratio (1) measured on the surface of stainless steel containing 15 wt % or more of Cr by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source under the condition where the emission angle of photoelectrons is 12° to 85° is 0.08 or more, wherein the band gap energy of the surface oxide layer of the stainless steel is 2 eV or less: (1) wherein the Cr hydroxide represents CrOOH, Cr(OH)2 or Cr(OH)3, the atomic concentration is expressed in atomic %, and The total oxides and hydroxides include Cr oxide, the Cr hydroxide, Fe oxide, Fe hydroxide and metal oxides MO, and the metal oxides MO encompass mixed oxides, wherein M represents alloying elements or combinations thereof other than Cr and Fe in the matrix, and O represents oxygen.

2. The stainless steel having excellent surface conductivity for a fuel cell separator according to claim 1, wherein the value of the surface oxide atomic ratio (1) is 0.2 or more. 3 . The stainless steel having excellent surface conductivity for a fuel cell separator according to claim 1 , wherein a surface oxide layer of the stainless steel forms an ohmic contact with the substrate.

4. A method for manufacturing the stainless steel having excellent surface conductivity for a fuel cell separator according to claim 1, the method comprising: a primary surface treatment, wherein the primary surface treatment is performed by immersing the cold-rolled stainless steel sheet in a non-oxidizing acid solution or performing an electrolytic treatment after the immersion, and The secondary surface treatment is performed by immersing the cold-rolled stainless steel sheet in an oxidizing acid solution.

5. The method according to claim 4, wherein the primary surface treatment comprises immersing the cold-rolled stainless steel plate in the non-oxidizing acid solution for 5 seconds or longer, or heating the cold-rolled stainless steel plate at 0.1 A / cm 2 or greater current density for 5 seconds or longer, and The non-oxidizing acid solution is a 5 wt % or greater hydrochloric acid solution or a sulfuric acid solution at 50° C. or higher. acid solution.

6. The method according to claim 4, wherein the secondary surface treatment comprises immersing the cold-rolled stainless steel sheet in the oxidizing acid solution for 5 seconds or longer, and The oxidizing acid solution is a 5 wt % or greater nitric acid solution at 50° C. or higher.

Citation Information

Patent Citations

  • Stainless steel for fuel cell separator plate and manufacturing method therefor

    CN107925040A